Is there variation in health care for children and young people with cerebral palsy across the North of England? An audit of clinical practice. (24th May 2012) - Balu, R; Horridge, KA; Tennant, PWG; Rankin, J; Bythell, M; Hiley, C; Braun, T
Abstract : Aims: To establish whether there is variation in health care for children and young people with cerebral palsy (CP) across the north of England. Methods: Retrospective case note review of 389 children and young people registered on the North of England Collaborative Cerebral Palsy Survey (NECCPS) living in 15 geographical districts, born 1995-2002, with subsequent data validation by clinicians involved in their care. Data was collected on magnetic resonance imaging (MRI) of brain (marker of aetiological assessment), hips, spines, pain, growth, and nutrition. Results: The audit sample was representative of all children and young people registered with the NECCPS across a range of clinical and demographic factors. 221/389 (56.8%) children and young people had an MRI overall, with significant variation (p<0.001) in MRI rates between districts (figure 1 ). 259/389 (66.6%) had a discussion about pain recorded within the last 2 years. 110/126 (87.3%) cases where pain was present, had a management plan (figure 2 ). Those from the socio-economically most deprived quintile were significantly (p<0.05) less likely to have had a discussion about pain than those in the least deprived quintile (figure 3 ). 69/373 (18.5%) had some degree of hip migration, of which 20.3% had complete hip dislocation. There was no record of hip status in 16/389 (4.1%). There was significant (p<0.01) variation between districts in recording of state of spine; there was no record in 24.4% of the sample. 31/66 (47%) of those with a spinal curvature were monitored by a spinal surgeon and 54/353 (33.1%) had their hips monitored by an orthopaedic surgeon, with inter-district variation in access to spinal and orthopaedic surgeons. 35/383 (9.1%) had received gastrostomy for feeding but there was no difference in Body Mass Index between this group and the rest of the sample. Only for 60% of the sample, weight was recorded within the last year. 119/389 (31%) had weight percentiles ascertained and recorded with a significant (p<0.001) inter-district variation (figure 4 ). Conclusion: There is variation in important aspects of health care for children and young people with cerebral palsy across the north of England. There is a need to work towards more equitable health care for the best health outcomes.